Effects of sea ice on Baltic Sea eutrophication - Ove Parn; Olaf Duteil; Elisa Garcia-Gorriz; Nuno Ferreira-Cordeiro; Gennadi Lessin; Diego Macias; Svetla Miladinova; Chiara Piroddi; Luca Polimene; Natalia Serpetti; Adolf Stips (Marine Pollution Bulletin, 2024)

Determining the distribution and accumulation patterns of floating litter in the Baltic Sea using modelling tools - Ove Pärn; Diego Macias Moy; Adolf Stips (Marine Pollution Bulletin, 2023)

Effects of Nutrient Management Scenarios on Marine Eutrophication Indicators: A Pan-European, Multi-Model Assessment in Support of the Marine Strategy Framework Directive - René Friedland; Diego Macias; Gianpiero Cossarini; Ute Daewel; Claude Estournel; Elisa Garcia-Gorriz; Bruna Grizzetti; Marilaure Grégoire; Bo Gustafson; Sofia Kalaroni; Onur Kerimoglu; Paolo Lazzari; et al. (Frontiers in Marine Science, 2021)
A novel pan-European marine model ensemble was established, covering nearly all seas under the regulation of the Marine Strategy Framework Directive (MSFD), with the aim of providing a consistent assessment of the potential impacts of riverine nutrient reduction scenarios on marine eutrophication indicators. For each sea region, up to five coupled biogeochemical models from institutes all over Europe were brought together for the first time. All model systems followed a harmonised scenario approach and ran two simulations, which varied only in the riverine nutrient inputs. The load reductions were evaluated with the catchment model GREEN and represented the impacts due to improved management of agriculture and wastewater treatment in all European river systems. The model ensemble, comprising 15 members, was used to assess changes to the core eutrophication indicators as defined within MSFD Descriptor 5. In nearly all marine regions, riverine load reductions led to reduced nutrient concentrations in the marine environment. However, regionally the nutrient input reductions led to an increase in the non-limiting nutrient in the water, especially in the case of phosphate concentrations in the Black Sea. Further core eutrophication indicators, such as chlorophyll-a, bottom oxygen and the Trophic Index TRIX, improved nearly everywhere, but the changes were less pronounced than for the inorganic nutrients. The model ensemble displayed strong consistency and robustness, as most if not all models indicated improvements in the same areas. There were substantial differences between the individual seas in the speed of response to the reduced nutrient loads. In the North Sea ensemble, a stable plateau was reached after only three years, while the simulation period of eight years was too short to obtain steady model results in the Baltic Sea. The ensemble exercise confirmed the importance of improved management of agriculture and wastewater treatments in the river catchments to reduce marine eutrophication. Several shortcomings were identified, the outcome of different approaches to compute the mean change was estimated and potential improvements are discussed to enhance policy support. Applying a model ensemble enabled us to obtain highly robust and consistent model results, substantially decreasing uncertainties in the scenario outcome.

Effects of Nutrient Management Scenarios on Marine Food Webs: A Pan-European Assessment in Support of the Marine Strategy Framework Directive - Chiara Piroddi; Ekin Akoglu; Eider Andonegi; Jacob W. Bentley; Igor Celić; Marta Coll; Donna Dimarchopoulou; René Friedland; Kim de Mutsert; Raphael Girardin; Elisa Garcia-Gorriz; Bruna Grizzetti; et al. (Frontiers in Marine Science, 2021)
Eutrophication is one of the most important anthropogenic pressures impacting coastal seas. In Europe, several legislations and management measures have been implemented to halt nutrient overloading in marine ecosystems. This study evaluates the impact of freshwater nutrient control measures on higher trophic levels (HTL) in European marine ecosystems following descriptors and criteria as defined by the Marine Strategy Framework Directive (MSFD). We used a novel pan-European marine modeling ensemble of fourteen HTL models, covering almost all the EU seas, under two nutrient management scenarios. Results from our projections suggest that the proposed nutrient reduction measures may not have a significant impact on the structure and function of European marine ecosystems. Among the assessed criteria, the spawning stock biomass of commercially important fish stocks and the biomass of small pelagic fishes would be the most impacted, albeit with values lower than 2.5%. For the other criteria/indicators, such as species diversity and trophic level indicators, the impact was lower. The Black Sea and the North-East Atlantic were the most negatively impacted regions, while the Baltic Sea was the only region showing signs of improvement. Coastal and shelf areas were more sensitive to environmental changes than large regional and sub-regional ecosystems that also include open seas. This is the first pan-European multi-model comparison study used to assess the impacts of land-based measures on marine and coastal European ecosystems through a set of selected ecological indicators. Since anthropogenic pressures are expanding apace in the marine environment and policy makers need to use rapid and effective policy measures for fast-changing environments, this modeling framework is an essential asset in supporting and guiding EU policy needs and decisions.

Seasonal and Inter-Annual Variability of the Phytoplankton Dynamics in the Black Sea Inner Basin - Svetla Miladinova; Adolf Stips; Diego Macias Moy; Elisa Garcia-Gorriz (Oceans, 2020)
We explore the patterns of Black Sea phytoplankton growth as driven by the thermohaline structure and circulation system and the freshwater nutrient loads. Seasonal and inter-annual variability of the phytoplankton blooms is examined using hydrodynamic simulations that resolve mesoscale eddies and online coupled bio-geochemical model. This study suggests that the bloom seasonality is homogeneous across geographic locations of the Black Sea inner basin, with the strongest bloom occurring in winter (February–March), followed by weaker bloom in spring (April–May), summer deep biomass maximum (DBM) (June–September) and a final bloom in autumn (October–November). The winter phytoplankton bloom relies on vertical mixing of nitrate from the intermediate layers, where nitrate is abundant. The winter bloom is highly dependent on the strength of the cold intermediate layers (CIL), while spring/summer blooms take advantage of the CIL weakness. The maximum phytoplankton transport across the North Western Shelf (NWS) break occurs in September, prior to the basin interior autumn bloom. Bloom initiation in early autumn is associated with the spreading of NWS waters, which in turn is caused by an increase in mesoscale eddy activity in late summer months. In summary, the intrusion of low salinity and nitrate-rich water into the basin interior triggers erosion of the thermocline, resulting in vertical nitrate uplifting. The seasonal phytoplankton succession is strongly influenced by the recent CIL disintegration and amplification of the Black Sea circulation, which may alter the natural Black Sea nitrate dynamics, with subsequent effects on phytoplankton and in turn on all marine life.

Obtaining the correct sea surface temperature: bias correction of regional climate model data for the Mediterranean Sea - Diego Macias; Elisa Garcia-Gorriz; Alessandro Dosio; Adolf Stips; Klaus Keuler (Climate Dynamics, 2018)

The seasonal cycle of the Atlantic Jet dynamics in the Alboran Sea: direct atmospheric forcing versus Mediterranean thermohaline circulation - Diego Macias; Elisa Garcia-Gorriz; Adolf Stips (Ocean Dynamics, 2016)

Productivity changes in the Mediterranean Sea for the twenty-first century in response to changes in the regional atmospheric forcing - Diego M. Macias; Elisa Garcia-Gorriz; Adolf Stips (Frontiers in Marine Science, 2015)

Simulating the temporal and spatial dynamics of the North Sea using the new model GETM (general estuarine transport model) - Adolf Stips; Karsten Bolding; Thomas Pohlmann; Hans Burchard (Ocean Dynamics, 2004)

Microscale distribution of zooplankton in relation to turbulent diffusion - Marie Maar; Torkel Gissel Nielsen; Adolf Stips; AndréW. Visser (Limnology and Oceanography, 2003)
Microscale vertical distribution of proto‐and mesozooplankton in relation to turbulent diffusion was investigated using a high‐resolution sampler (HSR) during cruises in the Skagerrak, Denmark, and the Northern Aegean, Greece. A strong pycnocline and a deep chlorophyll maximum (DCM) characterized both areas. The phytoplankton biomass in the Skagerrak was much higher and dominated by netplankton compared with the Aegean, where picoplankton dominated. Deployments of the HRS and measurements of microscale turbulence were made simultaneously in the mixed surface layer, the pycnocline, and the DCM and revealed a large range (0.2‐250 cm 2 s −1 ) in turbulent diffusion. In general, turbulent diffusion was highest in the surface layer. The variability of the plankton organisms within the 3‐m strata sampled by the HRS was quantified by their coefficient of variation (CV = SD/mean) and analyzed with respect to turbulent diffusion. We hypothesized that the variability of the vertical distribution would be independent of turbulence up to a threshold where dispersion overwhelms the swimming ability of the organism and variability decreases. The hypothesis was confirmed by our results; for the weak swimmers, ciliates, Ceratium spp., and nauplii, there was a significant decrease in CV with increasing turbulence, whereas the variability of the stronger swimmer represented by copepodites was uncorrelated with turbulent diffusion. This underscores the potential of these organisms in locating and exploiting food patches in the water column.

Development of a deep chlorophyll maximum of Heterocapsa triquetra Ehrenb. at the entrance to the Gulf of Finland - Kaisa Kononen; Maija Huttunen; Seija Hällfors; Patrick Gentien; Michel Lunven; Timo Huttula; Jaan Laanemets; Madis Lilover; Juss Pavelson; Adolf Stips (Limnology and Oceanography, 2003)
The development of a deep chlorophyll maximum (DCM) at a depth of 30–35 m was followed during a 15‐d case study in July 1998 at the entrance to the Gulf of Finland. The study consisted of three 18–24‐h periods of biological (chlorophyll a , phytoplankton, primary production), chemical (nitrate, phosphate) and physical (CTD, turbulence, vertical particle size distribution) measurements at an anchor station and six mesoscale towed CTD/ fluorometer mappings over the surrounding area. Exceptionally cold and windy weather led to a red tide of the dinoflagellate Heterocapsa triquetra instead of the cyanobacterial bloom that frequently occurs in late summer. Comparison of the estimated amount of nitrogen required for an H. triquetra bloom biomass with external loading affirmed that the bloom had been formed on the basis of the nitrate pool below the thermocline. The development of the bloom, therefore, led to the extremely deep nitracline. The DCM formed by H. triquetra developed at the top of the nitracline at an illumination of H. triquetra after an upwelling event that fertilized the upper layer with phosphorus.

Modelling of convective turbulence with a two-equation k-ε turbulence closure scheme - Adolf Stips; Hans Burchard; Karsten Bolding; Walter Eifler (Ocean Dynamics, 2002)

Dissipation and mixing in a coastal jet: A Baltic Sea case study - Christoph Zülicke; Eberhard Hagen; Adolf Stips (Aquatic Sciences, 1998)

Test measurements with an operational microstructure-turbulence profiler: Detection limit of dissipation rates - Hartmut Prandke; Adolf Stips (Aquatic Sciences, 1998)